Winter Bird Diversity and Habitat Characteristics\nin North Campus of Xichang College - Ang Lan Qi Dongming Wang Jing Tang Wei Feng Xi Yuan Li (Ye Sheng Dong Wu Xue Bao = Chinese Journal of Wildlife, 2015)
We investigated the bird species in 5 habitats,viz.shrub-forest,open forest-shrub,turf,water,and building area by line transect method from November 2013 to January 2014 on the north campus of Xichang College.We recorded 57 species of 7 orders and 26 families.There were 43 residents,7 summer migrants,4 winter migrants and 4 passage migrants.There were 13 Palaearctic species,34 Oriental species and 10 widespread species.The dominant species were little egret(Egretta garzetta),Eurasian tree sparrow(Passer montanus)and red-vented bulbul(Pycnonotus cafer stanfordi).Highest bird diversity was 3.025 in the shrub and forest,and the lowest was 1.669 in the building area.The most similar bird communities were shrub-forest and open forest-shrub(0.538),and the least similar were shrub-forest and water(0.077).We analyzed the effects of habitat type on bird diversity and make recommendations for bird conservation on the campus.\n